The Union of Spanish Professors in Exile - Claret Miranda, Jaume (Historia y Memoria de la Educación, 2019)
After the Spanish Civil War, thousands of people took the path of exile, including an important group of prominent professors and university researchers. Their number led them to create the Union of Spanish Professors in Exile (UPUEE) with the double objective of creating a network of mutual support and presenting itself as the legitimate alternative –academically and politically— to the Francoist university. With the beginning of the Second World War, its activity was transferred mostly to the American republics and in the Autumn of 1943 a first Congress was held in Cuba to consolidate the founding objectives, in the confidence that an Allied victory would allow them to return to Spain and to lead the scientific and democratic recovery. While the so-called Declaración de la Habana represents the height of its influence, the continuity and progressive normalization of the Spanish dictatorship only brought their disappointment. The UPUEE would not survive the Cold War. This article analyzes the history, trajectory and legacy of this organization.